Case study: radiological evidence of intracisternal bleed spread into brain perivascular spaces - Nagesh C. Shanbhag; Harisinh Parmar; Vishal K. Salve; Iype Cherian (Academia Medicine)
Background: Basal cisternostomy (BC) involves opening cisterns (cerebrospinal fluid, CSF-filled spaces) to atmospheric pressure using a skull base approach to alleviate brain edema in severe brain injuries such as subarachnoid hemorrhage (SAH). Cisterns are in direct continuity with brain perivascular spaces (PVS) that form highways for the brain-wide solute clearance pathway termed the glymphatic system. The CSF-shift edema hypothesis proposes that there is a shift in CSF from cisterns at high pressure to the brain interstitial space via PVS at low pressure under severe-brain-injury conditions contributing to edema progression and aggravating brain damage. Case presentation: We report for the first time radiological evidence of CSF shift in recent aneurysmal SAH (aSAH) into the dilated PVS of subcortical vessels in a 55-year-old patient. Fischer grade 3 and WFNS grade 2 SAH was managed by clipping the left middle cerebral artery (M1) segment aneurysm preceded by BC using a pterional craniotomy approach. Postoperative neurological improvement was evident (WFNS grade 1) with a reduction from moderate disability (preoperatively) to no disability 20 months post-surgery. Conclusions: The progression of aSAH bleeding from basal cisterns into dilated subcortical PVS provided the first in vivo evidence of the CSF-shift hypothesis, allowing new avenues to explore the human glymphatic system and PVS-CSF dynamics. BC could potentially underpin the glymphatic concept of brain solute transport and its exchange, warranting further investigations.